Effects of azoxystrobin, chlorothalonil, and ethoprophos on the reproduction of three terrestrial invertebrates using a natural Mediterranean soil - Leitão, Sara (2014)
The potential terrestrial toxicity of three pesticides, azoxystrobin, chlorothalonil, and ethoprophos was evaluated using reproduction ecotoxicological tests with different non-target species: the collembolan Folsomia candida, the earthworm Eisenia andrei, and the enchytraeid Enchytraeus crypticus. All reproduction tests were performed with natural soil from a Mediterranean agricultural area (with no pesticide residues) in order to improve the relevance of laboratory data to field conditions. Controls were performed with natural and standard artificial soil (OECD 10% OM). The fungicide azoxystrobin showed the highest toxicity to earthworms (EC50 = 42.0 mg a.i. kg−1 dw soil). Collembolans were the most sensitive taxa in terms of sublethal effects of chlorothalonil with an EC50 of 31.1 mg a.i. kg−1 dw soil followed by the earthworms with an EC50 of 40.9 mg a.i. kg−1 dw soil. The insecticide ethoprophos was the most toxic to collembolans affecting their reproduction with an EC50 of 0.027 mg a.i. kg−1 dw soil. Enchytraeids were generally the least sensitive of the three species tested for long-term effects. Earthworms were not always the most sensitive species, emphasizing the need to increase the number of mandatory assays with key non-target organisms in the environmental risk assessment of pesticides.